2019
DOI: 10.3390/ijms20153726
|View full text |Cite
|
Sign up to set email alerts
|

The Human Coronary Collateral Circulation, Its Extracardiac Anastomoses and Their Therapeutic Promotion

Abstract: Cardiovascular disease remains the leading global cause of death, and the number of patients with coronary artery disease (CAD) and exhausted therapeutic options (i.e., percutaneous coronary intervention (PCI), coronary artery bypass grafting (CABG) and medical treatment) is on the rise. Therefore, the evaluation of new therapeutic approaches to offer an alternative treatment strategy for these patients is necessary. A promising research field is the promotion of the coronary collateral circulation, an arterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 124 publications
0
8
0
Order By: Relevance
“…Taken together, accumulating evidence suggests that well-developed collateral circulation contributes positively to the course of coronary artery disease. Recently, a large body of evidence has indicated that the presence of an extensive collateral circulation has been associated with the decrease of myocardial infarction in patients with stable CAD [9]. The most widely used invasive method for assessing coronary collateral circulation is contrast angiography.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, accumulating evidence suggests that well-developed collateral circulation contributes positively to the course of coronary artery disease. Recently, a large body of evidence has indicated that the presence of an extensive collateral circulation has been associated with the decrease of myocardial infarction in patients with stable CAD [9]. The most widely used invasive method for assessing coronary collateral circulation is contrast angiography.…”
Section: Discussionmentioning
confidence: 99%
“…Coronary collateral circulation (CCC) was evaluated by the Rentrop classification method. 11 The criterias of this method are as follows: grade 0, no filling of contrast; grade one, filling of side branches of collateral with no epicardial perfusion; grade two, partial filling of epicardial artery by collateral; grade three, fully filling of epicardial artery. 11 Good coronary collateral circulation (CCC) was delineated as grade two or grade three collateral, poor CCC was delineated as grade 0 or grade one collateral.…”
Section: Methodsmentioning
confidence: 99%
“…The formation of CCC is affected by various factors, including chronic myocardial ischemia, changes in blood flow pressure gradient, and the effect of inflammatory factors 3 . In addition, comorbidities such as hypertension and diabetes, as well as physical exercise training and growth factors, have also been reported to influence CCC development 4,5 . C‐reactive protein (CRP) and red cell distribution width (RDW) have recently been reported to have a close relationship with CCC formation 6,7 .…”
Section: Introductionmentioning
confidence: 99%